Experience of Foreign Countries in the Development of Kinetic Intelligence of Students - Surayyo, Umirzokova (Indonesian Journal Publisher, 2024)
The article reflects on the results of research on the experience of foreign countries on the development of kinetic intelligence among students. Methods and approaches used in different countries to encourage physical activity, sports and creativity among students of higher educational institutions are analyzed. Also, the practice of applying the best practices used in foreign educational institutions in the educational system of our country was studied.